Studi tentang Akuntabilitas Pengelolaan Alokasi Dana Desa di Maccini Baji, Kabupaten Jeneponto - Ridwan, Muhammad; Anwar, Samsinar; Idrus, Mukhammad (Universitas Negeri Makassar, 2022)
This study aims to describe the accountability of village fund allocation management. Data collection was carried out using in-depth interview methods, observation methods and documentation methods in the form of 2018 village financial management reports and other supporting reports. Data analysis was performed using descriptive analysis. The results of this study indicate that in the village fund allocation planning process the principles of participation and transparency have been implemented, the process of implementing village fund allocations has applied the principles of transparency and accountability, and the reporting and accountability process for village fund allocation has applied the principle of accountability.Penelitian ini bertujuan untuk mendeskripsikan akuntabilitas pengelolaan alokasi dana desa. Pengumpulan data dilakukan dengan menggunakan metode wawancara mendalam, metode observasi dan metode dokumentasi berupa laporan pengelolaan keuangan desa 2018 dan laporan pendukung lainnya. Analisis data dilakukan dengan menggunakan analisis deskriptif. Hasil penelitian ini menunjukkan bahwa dalam proses perencanaan alokasi dana desa prinsip partisipasi dan transparansi telah diterapkan, proses pelaksanaan alokasi dana desa telah menerapkan prinsip transparansi dan akuntabilitas, dan proses pelaporan dan akuntabilitas alokasi dana desa. telah menerapkan prinsip akuntabilitas.